2020
DOI: 10.3390/bios10110164
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Vasodilation as Potential Diagnostic Biomarker in Breast Cancer Using Deep Learning-Driven Thermomics

Abstract: Breast cancer is the most common cancer in women. Early diagnosis improves outcome and survival, which is the cornerstone of breast cancer treatment. Thermography has been utilized as a complementary diagnostic technique in breast cancer detection. Artificial intelligence (AI) has the capacity to capture and analyze the entire concealed information in thermography. In this study, we propose a method to potentially detect the immunohistochemical response to breast cancer by finding thermal heterogeneous pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…Deep radiomics is known for its tendency of having high dimensionality, thereby intensifying the possibility of overfitting a decision-making unit (i.e., the random forest model in this study) and the curse of dimensionality problem. The proposed ConvAE provided low-dimensional deep radiomics by spanning the imaging features to a lower-dimensional space [ 54 ]. We applied dimensionality reduction for the conventional radiomics by following the traditional way to shrink features while preserving the image characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep radiomics is known for its tendency of having high dimensionality, thereby intensifying the possibility of overfitting a decision-making unit (i.e., the random forest model in this study) and the curse of dimensionality problem. The proposed ConvAE provided low-dimensional deep radiomics by spanning the imaging features to a lower-dimensional space [ 54 ]. We applied dimensionality reduction for the conventional radiomics by following the traditional way to shrink features while preserving the image characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…It lowers the accuracy while showing pseudo improvement in the overall accuracy of the system due to the increased collinearity among the features. To alleviate this problem, one potential solution is to use deep-learning feature selection for deep radiomics [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors 8,9 in previous work demonstrated use of equivalent wave field transform (EWFT) applied to dynamic data to detect increased perfusion associated with the tumor.…”
Section: Breast Thermographymentioning
confidence: 99%
“…In [24], a new method for detecting the immunohistochemical response of breast cancer was proposed. The proposed method works by finding heterogeneous thermal patterns in the target area.…”
Section: Related Workmentioning
confidence: 99%